Digital Based Education and Counseling on Self-Care Behaviors in Patients with Type 2 Diabetes Mellitus as a Prevention Strategy for Neuropathy Complications - Asnuddin; Yenny Puspitasari; Prima Dewi Kusumawati; Yammar (Journal Of Nursing Practice, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is the most common type of diabetes, accounting for approximately 90% of all diabetes cases. It is characterized by insulin resistance, where the body fails to adequately respond to insulin. Complications can include macrovascular and microvascular damage, as well as diabetic neuropathy, which can occur in both newly diagnosed and long-standing patients. Purpose: This study aims to explain the influence of digital-based education and counseling on self-care behaviors in patients with T2DM as a prevention strategy for neuropathy complications. Methods: This study used a quasi-experimental design with a two-group pretest posttest design, where the pretest was implemented before treatment digital education and counseling, the posttest was implemented after treatment digital education and counseling. the posttest was implemented after treatment digital education and counseling. This study was conducted with pretest observation before education on self-care for patients with T2DM was implemented. Results: The study population consisted of 194 patients with T2DM in the Lawawoi Community Health Center area, from which 32 respondents were selected via purposive sampling. Data were collected through questionnaires The Summary of Diabetes Self Care Activities (SDSCA) Reliabilitas: Cronbach’s alpha antara 0.62 – 0.91 Validated by experts with a score of CVI (Content Validity Index) > 0.80, Level of knowledge validated by experts, CVI > 0.80. Reliabilitas: Cronbach’s alpha berkisar antara 0.70 – 0.85, shows good internal consistency, and analyzed using paired t-tests and independent samples t-tests. Conclusion: The findings revealed that the digital education group’s knowledge obtained a sig. (2 tailed) value on the pretest and posttest of 0.000 <0.05, the digital education group’s skills obtained a sig. (2 tailed) value on the pretest and posttest of 0.000 <0.05, the counseling group’s knowledge obtained a sig. (2 tailed) value on the pretest and posttest of 0.000 <0.05, while the counseling group’s skills obtained a sig. (2 tailed) value on the pretest and posttest of 0.000 <0.05. There is a significant influence of digital-based education and counseling on the knowledge and skills of patients with T2DM.